2011
DOI: 10.1002/chem.201100045
|View full text |Cite
|
Sign up to set email alerts
|

A Heteroleptic Bis(tridentate) Ruthenium(II) Complex of a Click‐Derived Abnormal Carbene Pincer Ligand with Potential for Photosensitzer Application

Abstract: [a] Ruthenium(II) polypyridyl complexes have received particular interest with respect to photosensitizer applications, because they are stable and inert complexes that show a defined metal-to-ligand charge transfer (MLCT).[1] A central dilemma is that trisbidentate complexes (e.g., of 2,2'-bipyridine, bpy) show long excited-state lifetimes, whereas bis(tridentate) complexes (e.g., of 2,2':6',2''-terpyridine, tpy) allow the isomer-free construction of linear assemblies for vectorial electron-transfer proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
98
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(99 citation statements)
references
References 54 publications
1
98
0
Order By: Relevance
“…Solvent choice has relatively little effect on yields, and it appears to be a matter of preference and, sometimes, solubility of starting materials that determines the choice of solvent systems. Alcohols like ethanol 87,95,97,98 and tert-butyl alcohol 93,94,96 mixed with water are most common in the literature, while DMSO (with 99 or without 100 water), THF, 60 CH 3 CN 101 and DMF 70,91 are also attested.…”
Section: Alkynesmentioning
confidence: 99%
See 2 more Smart Citations
“…Solvent choice has relatively little effect on yields, and it appears to be a matter of preference and, sometimes, solubility of starting materials that determines the choice of solvent systems. Alcohols like ethanol 87,95,97,98 and tert-butyl alcohol 93,94,96 mixed with water are most common in the literature, while DMSO (with 99 or without 100 water), THF, 60 CH 3 CN 101 and DMF 70,91 are also attested.…”
Section: Alkynesmentioning
confidence: 99%
“…59,60,93,95,97,98,100,105,106,111,128,129 Flood and co-workers showed that Ru(II) forms stable coordination compounds with 3b. X-ray crystal crystallography showed a 1 : 2 metal : ligand stoichiometry, with the ligands adopting a distorted octahedral geometry, as demonstrated in Fig.…”
Section: Rutheniummentioning
confidence: 99%
See 1 more Smart Citation
“…[7] However, tridentate bisMICs have not been isolated, although a silver-stabilized carbene was reported as an intermediate in the synthesis of a series of luminescent ruthenium complexes by Schubert et al [8] Bertrand et al reported the structure of a potassium-stabilized tridentate MIC. [9] In this paper, we report the first isolation of free tridentate carbenes and an iron complex.…”
Section: Introductionmentioning
confidence: 99%
“…Click-derived 3,107 ligands have been introduced as analogs of polypyridyl ligands, in particular of terpyridine (tpy), 96,[108][109][110][111] and successfully used to produce tridentate cyclometalating polypyridyl ligands, namely 1,3-dipyridylbenzene. In this respect, aryl azides react with diethynylbenzene building blocks, in good yields using a standard click procedure.…”
mentioning
confidence: 99%